The postcommunist economic transformation essays in honor of Gregory Grossman (Westview Press, 1994)
The ongoing effort to transform the centrally planned economies of the postcommunist east into market economies has dashed early hopes that it would be possible to formulate a design and an agenda for marketization and privatization, to manage the process rationally, and to emerge from the turmoil of structural change fairly quickly. This volume takes a sober second look at approaches to and prospects for making the transition to new economic systems. The contributing authors, distinguished specialists on the formerly planned economies with decades of experience in the field, offer cogent analyses of the economic, political, social, and geographic dimensions of current reforms. They also review salient features of the old command economic systems, the effects of which even today have not been eradicated. The authors' intimate knowledge of how the old systems functioned gives them a special appreciation both of the need for reform and of the cultural and political legacies that are shaping and distorting the reform process. They are acutely aware of the difficulty of imposing Western policies in the absence of Western institutions, and their essays sound a note of skepticism about the feasibility of rebuilding these economies with a simple reliance on the market plus macro-economic guidance.